Revised spectral metrics for body surface measurements of gastric electrophysiology. Issue 3 (21st November 2022) - Schamberg, Gabriel; Varghese, Chris; Calder, Stefan; Waite, Stephen; Erickson, Jonathan; O'Grady, Greg; Gharibans, Armen A.
Abstract: Background: Electrogastrography (EGG) non‐invasively evaluates gastric function but has not achieved common clinical adoption due to several technical limitations. Body Surface Gastric Mapping (BSGM) has been introduced to overcome these limitations, but pitfalls in traditional metrics used to analyze spectral data remain unaddressed. This study critically evaluates five traditional EGG metrics and introduces improved BSGM spectral metrics, with validation in a large cohort. Methods: Pitfalls in five EGG metrics were assessed (dominant frequency, percentage time normogastria, amplitude, power ratio, and instability coefficient), leading to four revised BSGM spectral metrics. Traditional and revised metrics were compared to validate performance using a standardized 100‐subject database of BSGM tests (30 min baseline; 4‐h postprandial) recorded using Gastric Alimetry® (Alimetry). Key Results: BMI and amplitude were highly correlated ( r = −0.57, p < 0.001). We applied a conservative BMI correction to obtain a BMI‐adjusted amplitude metric ( r = −0.21, p = 0.037). Instability coefficient was highly correlated with both dominant frequency ( r = −0.44, p < 0.001), and percent bradygastria ( r = 0.85, p < 0.001), in part due to misclassification of low frequency transients as gastric activity. This was corrected by introducing distinct gastric frequency and stability metrics ( Principal Gastric Frequency and Gastric Alimetry Rhythm Index (GA‐RI) TM ) that were uncorrelated ( r = 0.14, p = 0.314). Only 28% of subjects showed a maximal averaged amplitude within the first postprandial hour. Calculating Fed:Fasted Amplitude Ratio over a 4‐h postprandial window yielded a median increase of 0.31 (IQR 0–0.64) above the traditional ratio. Conclusions & Inferences: The revised metrics resolve critical pitfalls impairing the performance of traditional EGG, and should be applied in future BSGM spectral analyses. Abstract : Metrics resolve critical pitfalls impairing the performance of traditional electrogastrography, and should be applied in future body surface gastric mapping spectral analyses.